THE EFFECT OF RELATIONSHIP MARKETING ON THE LOYALTY OF SUPPLIER OF TOBACCO WITH MANUAL DRYING IN PT. EXPORT LEAF INDONESIA - Saparwadi Saparwadi (Master of Management, Mataram University, 2016)
This research is aimed at analyzing the effect of relationship marketing on the commitment of company, communication of company and the complaint handling of PT. ELI on the loyalty of supplier of tobacco with manual drying in East Lombok. The data were collected through questionnaire and verified with validation and reliability test. The data then were analyzed using classic assumption, multiple linear regression, significance test, and certain use of parameter to proof the hypothesis. The research showed that there is partially and simultaneously significant effect of relationship marketing consisting of company commitment, company communication, and complaint handling of PT ELI on the loyalty of supplier of tobacco with manual drying in east Lombok. Of the relationship marketing of PT ELI that has a dominant effect of the loyalty of supplier in East Lombok is the commitment of company. The level of effect of commitment of company is 24.10 percent (the value of r2X1Y) on the loyalty of supplier. The simultaneous effect of the three dimensions of relationship marketing is 50.40 percents (R2 =0.504) on the loyalty of supplier, categorized as the high criteria. One of the suggestions for the management of PT ELI is to improve partnership with the supplier, with the concept that may be applied as well as possible in order that the partnership can give sustainable and high economic benefit for the farmers. Keywords: relationship, marketing (Company, commitment, communication, and complain handling) and loyalty of Supplier